The effects of different irrigation solutions on the bond strength of cemented fiber posts - Alkhudhairy FI; Yaman P; Dennison J; McDonald N; Herrero A; Bin-Shuwaish MS (Dove Medical Press, 2018)
Fahad I Alkhudhairy,1 Peter Yaman,2 Joseph Dennison,2 Neville McDonald,2 Alberto Herrero,3 Mohammed S Bin-Shuwaish1 1Department of Restorative Dental Sciences, College of Dentistry, King Saud University, Riyadh, Kingdom of Saudi Arabia; 2Department of Cariology, Restorative Sciences and Endodontics, School of Dentistry, University of Michigan, Ann Arbor, Michigan, USA; 3Biologic and Materials Sciences, School of Dentistry, University of Michigan, Ann Arbor, Michigan, USA Objective: To study effect of root canal irrigant solutions on the bond strength of cemented fiber posts, and resin cement-tags in root canal dentin.Materials and methods: Fifty-two human single-rooted anterior teeth were selected and stored in 1% sodium azide. Crowns were sectioned 2 mm incisal to the cemento enamel junction with diamond bur at high speed under water-cooling. After standard root canal treatment to tested teeth, they were randomly assigned into four groups (n=13) corresponding to the endodontic irrigant solution that was used during post space preparation. The treatment groups were: Group 1: 6.15% sodium hypochlorite; Group 2: 17% EDTA; Group 3: 6.15% NaOCl +17% EDTA; Group 4: 6.15% NaOCl +0.12% chlorhexidine solution. Parallel-sided fiber posts were used for all specimens. Samples were embedded in a cylindrical PVC mounting jig to facilitate perpendicular sectioning. With low speed diamond saw, cervical and apical specimens from each tooth were obtained and subjected to push-out test using universal testing machine. SEM was used to examine the root-canal dentin surface.Results: Statistical analysis revealed significant difference among the groups at P<0.05. Group 2 treated with EDTA, had the highest bond strength; 18.63±2.85 MPa in cervical specimens and 13.49±3.67 MPa in apical specimens. The cervical specimens of Groups 2 and 3 were significantly different than the apical specimens in the same group. Adhesive failure between cement and dentin was the main failure mode observed in all groups. Groups irrigated with EDTA showed cleaner dentin surface and better resin tag formation, while groups treated with NaOCl showed less resin tag formation and insufficient smear layer removal.Conclusion: NaOCl had adverse effect on bond strength of self-adhesive resin cement to radicular dentin. EDTA irrigant solution produced higher bond strength and was more effective in removing smear layer than NaOCl. Keywords: bond strength, fiber posts, irrigation solution, resin cement